Response of Two Cowpea Cultivars to Spraying with Moringa Leaf Extract and Jasmonic Acid in Growth Yield Components - Alshabbani, Karrar A D; Jaafar, Hayder S (South Eastern European Journal of Public Health, 2024)
A field experiment was conducted at the Research Station of the College of Agriculture, University of Kufa/Najaf, for the spring season of 2023, to determine the growth and yield response of two cowpea varieties to spraying with Moringa leaf extract and jasmonic acid (JA). The experiment included three factors, the first factor was two varieties of cowpea: American Ramshon and Dutch variety, the second factor was foliar spray with Moringa leaf extract at three concentrations of 0.2 and 4 g L-1, and the third factor was foliar spray with three concentrations of JA at 0, 10 and 20 mg L-1. The spraying was applied three times during the growing season, with an interval period of 14 days. The experiment was split-split-plots based on Randomized Complete Blocks Design (R.C.B.D) and three replicates. The results showed that the Dutch variety was significantly superior in the vegitative growth indicators, while the American cowpea Ramshon had the highest response in quantitative and chemical indicators, especially the total plant yield of green pods recording 7.470 tons ha-1 compared to 5.886 tons ha-1 for the Dutch variety. Spraying with Moringa leaf extract at a concentration of 4 g L-1 recorded significantly higher indicators in the shoot dry weight 65.59 g plant-1, number of pods 25.61 pods plant-1, and leaf and pods content of carbohydrates and protein 2.65 and 12.95%. On the other hand, foliar spray with JA at 20 mg L-1 recorded a significant increase in plant length 45.88 cm. Most of the studied indicators in the experiment recorded higher rates in the interaction treatment of the Dutch variety and spraying 4 g L-1 Moringa leaf extract and 10 mg L-1 of JA compared to all individual and interaction treatments.